Investigating the effects of agricultural best management practices on water quality of a surface water - Akıner Muhammed Ernur (Zaštita Materijala)
Water is an essential component of the Earth's ecosystem; each freshwater body has its specific physical and chemical characteristics. High contents of nutrients in the water, such as nitrogen and phosphorus are the major issues in terms of water quality. Notably, excessive nutrient concentrations in surface waters cause eutrophication. This research examines some pollution parameters to determine the current pollution level of the Göksu River. The river passes through the Göksu Delta, which is the most important natural habitat of the Mediterranean region of Turkey. Agricultural best management practices were an important phase of this study. The main goal was to examine the effects of agricultural best management practices on water quality of the Göksu River. Soil and Water Assessment Tool (SWAT) was used for modeling the water quality of the Göksu River considering the agricultural best management practices. Water quality is the lowest in the watershed outlet. For this reason, agricultural best management practices have been evaluated by using SWAT program by considering watershed outlet water quality values. Results confirmed that agricultural best management practices retain large amounts of nutrient load in the Göksu River Watershed. SWAT simulation shows that in case agricultural best management practices were used, there could be a high decrease in BOD5, NO2 - and Total P loads. Which means a higher water quality class according to the Surface Water Quality Management Regulations (SWQMR) of Turkey.